PROBLEMS OF QUALIFICATION OF THE CRIME OF NON-EXECUTION OF COURT DOCUMENTS AND IMPROVEMENT OF THE NORM ESTABLISHING LIABILITY - G. N. Dilmurodova (Ecominds Press, 2026)
This article analyzes in detail the issues of legal qualification of the crime of non-execution of court documents, its practical application and improvement of the regulatory and legal framework determining liability. In the course of the research, the Criminal Code of the Republic of Uzbekistan, judicial practice, as well as international experience were studied, shortcomings in existing legislation and problems in practical application were identified. The author developed recommendations on the correct qualification of cases of non-execution of court documents, a clear definition of criminal liability, as well as the creation of effective enforcement mechanisms. The results of the research serve to prevent crimes, increase the efficiency of the legal system and ensure fair judicial practice.
Keywords: Court documents, non-execution, crime, qualification, liability, legal norms, improvement, judicial practice, prevention.